O uso de história em quadrinhos para auxiliar no processo de ensino-aprendizagem da dengue - LIMA, Adriana Carvalho de (2024)
A story that can be part of everyday student was used to illustrate the process of teaching and learning about dengue. The aim was to analyze the applicability of the comic (comic), and interference in the same as teaching methodology in the educational activity. History was made containing matter about dengue and was given to elementary school students greater. The subjects participating in the study were 80 students of a municipal school in the municipality of Breves on Marajó Archipelago Pará. To analyze the use of history, two questionnaires were developed, applied before and after the use of this learning tool, whose responses were qualitatively analyzed. After application of comics, a considerable improvement was detected in the learning of students of the school where we apply the comic. This activity provided students with an enjoyable and meaningful educational activity.